2022
DOI: 10.1055/s-0042-1755262
|View full text |Cite
|
Sign up to set email alerts
|

The Current State of Targeted Muscle Reinnervation: A Systematic Review

Abstract: Background Targeted muscle reinnervation (TMR) is growing in popularity; however, literature evaluating patient characteristics and outcomes is limited. Methods The EMBASE database was queried with the search terms “targeted muscle reinnervation” OR “TMR” AND “outcomes” OR “patient outcomes.” Clinical human studies in English were eligible for inclusion, yielding 89 articles. After rigorous exclusion criteria, a total of 13 articles were included in this review. Study data including geographic locati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…Only one study incorporated validated functional assessment tools such as Orthotics Prosthetics User Survey (OPUS) and Neuro‐Quality of Life (Neuro‐QOL), which were reported as secondary outcomes (Mioton et al, 2020). A recent systematic review highlighted the need for standardized patient‐reported tools to understand long‐term patient experience following TMR (Walsh et al, 2023). Given the inextricable tie between LE amputation and function, this need is amplified in the LE TMR population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Only one study incorporated validated functional assessment tools such as Orthotics Prosthetics User Survey (OPUS) and Neuro‐Quality of Life (Neuro‐QOL), which were reported as secondary outcomes (Mioton et al, 2020). A recent systematic review highlighted the need for standardized patient‐reported tools to understand long‐term patient experience following TMR (Walsh et al, 2023). Given the inextricable tie between LE amputation and function, this need is amplified in the LE TMR population.…”
Section: Discussionmentioning
confidence: 99%
“…Two recent systematic reviews corroborate these findings through aggregate assessments of postoperative outcomes (McNamara & Iorio, 2020;Walsh et al, 2023). However, both reviews combine postoperative outcomes across UE and LE amputation populations, making it difficult to provide detailed analysis of intraoperative technique outcomes, and complications specific to the LE.…”
mentioning
confidence: 93%
“…TMR has now been demonstrated by multiple groups to treat RLP and PLP secondarily and to help prevent development of such pain when performed primarily at time of amputation. [32][33][34][35][36][37][38][39][40][41][42]47 This article is protected by copyright. All rights reserved.…”
Section: Introductionmentioning
confidence: 99%
“…TMR has now been demonstrated by multiple groups to treat RLP and PLP secondarily and to help prevent development of such pain when performed primarily at time of amputation. 1,2,[31][32][33][34][35][36][37][38][39]42 Our institution recently reported outcomes on 100 patients receiving primary TMR at time of below-the-knee amputation (BKA). 43 Our study found that, relative to 100 patients undergoing a BKA with traction neurectomy of all identified nerves, patients receiving TMR experienced significantly lower rates of overall pain, RLP, and PLP; decreased usage of narcotics; and increased ambulation.…”
mentioning
confidence: 99%
“…The novel concept of targeted muscle reinnervation (TMR) was first described in the early twenty-first century after a bilateral shoulder disarticulation amputee underwent brachial plexus nerve transfers to the pectoralis major and minor, demonstrating enhanced prosthesis control on electromyogram 11,12 . TMR uses the principles of reinnervation, by taking free nerve endings and coapting them into motor branches of deinnervated muscles, to prevent neuroma formation 1,13-16 . In other words, TMR “gives a free nerve somewhere to go and something to do.” TMR has been shown to reduce neuroma formation and chronic phantom limb pain and increase ambulatory rates, even in highly comorbid patients.…”
mentioning
confidence: 99%